GENETIC DIVERSITY OF Melica POPULATIONS AND THEIR STABILITY IN ECOLOGICAL LANDSCAPE (Applied Biological Research, 2023)
Melica grass has effective role in ecological landscape and its stability is affected  by population genetics. Main purpose of this study was to investigate the  relation and distance of Melica populations genetically that are grown in unlike  topographic and climatic conditions. Karyotyping and leaf storage protein SDS PAGE were employed to investigate the genetic diversity of 10 populations of 2  species of Melica viz., M. persica and M. jacquemontii as major plants in  ecological landscape of Esfahan, Alborz, Ghom, Golestan, Kerman and Yazd  habitats in Iran. The result of karyotyping showed that all the populations have  similar chromosomenumber(2n=2x=18), but cytogenetic parameters exhibited  significant differences in all the populations. Ward similarity analysis revealed  tions can be clustered into 4 groups. SDSPAGE of leaf  protein indicated that the population of M. persica ‘21856’ had highest  protein fragment while the lowest fragments belonged to M. jacquemontii [7683  and 10506]. Jaccard similarity coefficient revealed genetic variation in all the  studied populations of M. persica, but M. jacquemontii showed no variation. M.  persica had high diversity and more stability in ecological landscape and these  results suggest that the species of M. jacquemontii is a subspecies of M. persica.
Keywords: Climate; cytogenetic; diversity; natural habitat; population